2021
DOI: 10.1155/2021/7163598
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Control Technique for the Floor Heave in Goaf-Side Entry Retaining Based on Pressure Relief by Roof Cutting

Abstract: To solve the difficulty in controlling floor heave of a retained goaf-side roadway, a new control technique was investigated from the perspective of the pressure relief by roof cutting by combining mechanical analysis, numerical simulation, and engineering tests. The mechanical principle of controlling the floor heave based on pressure relief by roof cutting was attained by analyzing the movement of overlying strata and mechanical characteristics of key blocks before and after the roof cutting. A new technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…(a) An analysis of the floor heave dynamic monitoring showed that this phenomenon evolved with different intensities at different stages of the gateroad's life. This is generally consistent with previous studies [15,17,27,41]. The gateroad that was an object of study had no water inflows.…”
Section: Supporting Parameters and Deformation Of Gob-side Entry Reta...supporting
confidence: 91%
See 1 more Smart Citation
“…(a) An analysis of the floor heave dynamic monitoring showed that this phenomenon evolved with different intensities at different stages of the gateroad's life. This is generally consistent with previous studies [15,17,27,41]. The gateroad that was an object of study had no water inflows.…”
Section: Supporting Parameters and Deformation Of Gob-side Entry Reta...supporting
confidence: 91%
“…Many scholars have studied the floor heave mechanism in gob-side entry retaining [15][16][17]. It can be concluded that failure or plastic flow of the immediate floor, caused by stresses exceeding the strength limit of the rock, is a prerequisite for floor heave [18].…”
Section: Introductionmentioning
confidence: 99%
“…Since roadways are a key component of the production and transportation system in coal mines, improving their safety, reliability, and stability is of great importance for coal mine production. With the recent increase in coal mining depths and intensity; however, dynamic pressure phenomena such as rib spalling, floor heave, and roof fall have appeared frequently in roadway surrounding rock, posing serious threats to safety and efficient production [1][2][3][4]. In response, many scholars have intensively studied the dynamic pressure manifestation in coal mine roadways.…”
Section: Introductionmentioning
confidence: 99%